Information and Communications Technology in the 21st Century Classroom - Pérez Marín, Diana (De Gruyter, 2014)
Are you a student who wants to become an effective teacher in the 21st century? Maybe you are a teacher already? Would you like to learn how to take advantage of educational technologies in order to achieve your pedagogic goals? Nowadays, technology is all around us, but how do we, as teachers, make the best use of it? Technology has entered the classroom and most teachers are not trained in using it to achieve pedagogic goals. This book aims to remedy this situation. To do that, it provides the reader with many step-by-step guides and solved exercises, all written in clear language in a friendly, positive style. The book demystifies the whole process of understanding how new software or hardware works and introduces techniques to make the reader comfortable with classroom technologies. I hope that you enjoy it and find it useful. Dr. Diana Pérez Marín received a Ph.D. degree in Computer Science and Engineering from the Universidad Autonoma de Madrid in 2007. She has published more than 50 papers in journals, such as the Journal of Educational Technology, and Society and has authored the book "ICT in education" (in Spanish).